Insights into the Future of Young Professionals in the Irrigation and Drainage Sector: Outcomes from the Discussion on the ICID YP e‐Forum†. (11th December 2017) - Mersha, Adey Nigatu; Turunen, Mika; Heuvel, Kathleen
Abstract: The young generation of irrigation and drainage (I&D) sector professionals has an important role in ensuring sustainable and sufficient food production in the future. Currently, global food security faces challenges such as population growth, climate change and socio‐economic problems. Simultaneously, the interest of the young generation in agricultural water management is decreasing. The aim of this paper is to provide insight into the future and perspectives of the young professionals (YPs) by summarizing the key outcomes of discussions with YPs from the I&D sector from all continents. The discussions suggest that to ensure the availability of qualified professionals for the inherently multidisciplinary challenges of the future, opportunities for good quality education are necessary. Furthermore, the sector does not attract enough YPs towards education and careers in I&D. It is believed that adaptation of technology may improve the image of the sector and help showcase the innovative, challenging and rewarding opportunities that exist in the sector. Empowerment of women in the sector is seen to have a very high potential in capacity building. The discussions led to valuable conclusions on the role, challenges and future of women in the I&D sector. Education, research and innovation are seen as a necessity to ensure the availability of qualified experts to lead the industry into the future. Copyright © 2017 John Wiley & Sons, Ltd.